"Being a father": constructions of fatherhood by men with absent fathers. Issue 3 (2nd July 2020) - East, Leah; Hutchinson, Marie; Power, Tamara; Jackson, Debra
ABSTRACT: Family dynamics and parenting styles are influential on children's wellbeing [Walsh, F. (2016). Strengthening family resilience (3rd ed.). New York: Guilford Press]. Additionally, childhood experiences and how an individual experienced being parented can impact on how individuals as mothers and fathers choose to parent their own children [Herland, M. D., Hauge, M.-I., & Helegland, I. M. (2015). Balancing fatherhood: Experiences of fatherhood among men with a difficult past. Qualitative Social Work, 14 (2), 242–258]. However, growing up in a home with an absent parent may create challenges associated with parenting for individuals, due to not having these experiences themselves. Therefore, the article reports findings on men who grew up in a father-absent household and how their experiences influenced their understanding of fatherhood and becoming a father. Twenty-one men participated in this qualitative study. Findings revealed that although men felt unprepared for fatherhood they attempted to learn to be a father and expressed the importance of not wanting their children to experience father absence. The study findings provide important insights in the provision of support for fathers who have experienced father absence.